Foundations of a planned economy, 1926-1929 - Carr, Edward Hallett; Davies, R. W. (London : The Macmillian Press, 1969)
This text covers the last phase of the Tsarists regime, the ideological roots and origins of the Soviet regime, its establishment in power at the close of 1917 and its disintegration.
Volume I, Part II.
Includes bibliographical references and index.
kjo 18/01/2019
Loans
Keywords: History; Soviet Union